(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تمّ في هذا البحث دراسة استجابة و امتصاصية بعض المعادن (التوتياء ,النحاس, الحديد, الألمنيوم) المطلي سطحها المعرض للإشعاع المباشر فقط بطلاء أسود اللون ذي قدرة امتصاص عالية وانعكاسية منخفضة للإشعاع الوارد عليه, وذلك بسماكات طلاء مختلفة, (بغية الحصول على أجسام سوداء بأعلى امتصاصية) . وأجرينا القياس على القطع المعدنية بعد طلاء سطحها المعرض للإشعاع المباشر من أجل كل سماكة طلاء مأخوذة , وذلك في المختبر أولا عند مستوى سطح البحر باستخدام منبعين للضوء استطاعة الأول 30 واط , واستطاعة الثاني 100 واط وذلك لمقارنة امتصاصية هذه المعادن للإشعاع الصادر عن هذين المنبعين مع امتصاصيتها للإشعاع الصادر عن الشمس والتأكد من أن سيرورة الامتصاصية متماثلة في حالة الإشعاع الشمسي وحالة الإشعاع الصادر عن منبع ضوئي, ومن ثم أجرينا القياس في منطقة القدموس التي تقع على ارتفاع 900 مترٍ فوق سطح البحر باستخدام الإشعاع الشمسي المباشر. ومن ثم قمنا بإيجاد العلاقة بين الامتصاصية وسماكة الطلاء . In this research we studied and measured the response and absorbance for some metals (zinc, copper, iron, aluminum) which are exposed to the direct light and painted with black, which has a high absorbance and low emittance, and with different thicknesses (to obtain black bodies) with higher absorption. we took the measurement on the painted metals for each thickness of the paint in the laboratory first using tow lamps 30 watt and 100 watt to compare the absorption of these metals of the radiation from these two lamps with the absorption of the solar radiation and make sure that the absorption is similar of the two situations, then we took the measurements in AL- Kadmous Area which is 900m above sea level using direct solar radiation , and we found the relationship between the absorbance and the paint thickness.